Architecture for astronauts an activity-based approach - Häuplik-Meusburger, Sandra (SpringerWienNewYork, 2011)
Living and working in extra terrestrial habitats means being potentially vulnerable to very harsh environmental, social, and psychological, conditions. With the stringent technical specifications for launch vehicles and transport into space, a very tight framework for the creation of habitable space is set. These constraints result in a very demanding "partnership" between the habitat and the inhabitant